2003
DOI: 10.1182/blood-2002-07-2170
|View full text |Cite
|
Sign up to set email alerts
|

A 20-year perspective on the International Fanconi Anemia Registry (IFAR)

Abstract: Fanconi anemia (FA) is an autosomal recessive disorder characterized by cellular hypersensitivity to DNA cross-linking agents and cancer predisposition. Recent evidence for the interactions of ataxia-telangiectasia mutated protein ATM and breast cancer susceptibility proteins BRCA1 and BRCA2 (identified as FANCD1) with other known FA proteins suggests that FA proteins have a significant role in DNA repair/recombination and cell cycle control. The International Fanconi Anemia Registry (IFAR), a prospectively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

19
647
4
23

Year Published

2003
2003
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 676 publications
(703 citation statements)
references
References 42 publications
19
647
4
23
Order By: Relevance
“…17,20,21 Researchers have differentially found that individuals with either FANCG or FANCC mutations are at greater risk of severe cytopenia, whereas those with mutations in either FANCA or FANCG tend to have more somatic anomalies including skin and skeletal anomalies. 17,22 Genes appear to have been used as a proxy for specific mutations in most studies presumably because of the marked heterogeneity of FA with many mutations described within each causative gene and the difficulty in recruiting a patient cohort who are genetically homogeneous. Neveling et al (2009), 23 in a review article, focused on the genotype-phenotype correlations in FA and pointed out the futility in attempting these correlations using individual genes/complementation groups rather than specific mutations.…”
Section: Discussionmentioning
confidence: 99%
“…17,20,21 Researchers have differentially found that individuals with either FANCG or FANCC mutations are at greater risk of severe cytopenia, whereas those with mutations in either FANCA or FANCG tend to have more somatic anomalies including skin and skeletal anomalies. 17,22 Genes appear to have been used as a proxy for specific mutations in most studies presumably because of the marked heterogeneity of FA with many mutations described within each causative gene and the difficulty in recruiting a patient cohort who are genetically homogeneous. Neveling et al (2009), 23 in a review article, focused on the genotype-phenotype correlations in FA and pointed out the futility in attempting these correlations using individual genes/complementation groups rather than specific mutations.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Fifteen genes, defining 15 complementation groups, have been shown to be involved in FA. 4 One of them, FANCD1, corresponds to the BRCA2 gene, one of the main genes involved in autosomal dominant predisposition to breast and ovarian cancers.…”
Section: Introductionmentioning
confidence: 99%
“…The progressive BM failure and the late developing myeloid malignancies account for 90% of the mortality in FA [1]. Aside from cord blood transplantation [2], the only cure for the hematopoietic manifestations of FA is an HLA identical allogeneic BM transplantation from a family member, a therapy available to only about 30% of patients [3].…”
Section: Introductionmentioning
confidence: 99%
“…The identification of these genes raises the potential of using gene transfer technology to express the functional cDNA in autologous stem cells. The BM hypoplasia commonly observed in FA patients [1] and the reduced repopulating ability of stem cells in mice containing a disruption of the murine homologue of an FA gene [29,30] led to the hypothesis that autologous, geneticallycorrected stem cells would have an engraftment and proliferation advantage.…”
Section: Introductionmentioning
confidence: 99%